Cultivation-Dependant Assessment, Diversity, and Ecology of Haloalkaliphilic Bacteria in Arid Saline Systems of Southern Tunisia - El Hidri, Darine (Hindawi Publishing Corporation, 2013)
Haloalkaliphiles are polyextremophiles adapted to grow at high salt concentrations and alkaline pH values. In this work, we isolated 122 haloalkaliphilic bacteria upon enrichments of 23 samples from 5 distinct saline systems of southern Tunisia, growing optimally in media with 10% salt and at pH 10. The collection was classified into 44 groups based on the amplification of the 16S–23S rRNA internal transcribed spacers (ITS-PCR). Phylogenetic analysis and sequencing of the 16S rRNA genes allowed the identification of 13 genera and 20 distinct species. Three gram-positive isolates showing between 95 and 96% of 16S rRNA sequence homology with Bacillus saliphilus could represent new species or genus. Beside the difference in bacterial diversity between the studied sites, several species ecological niches correlations were demonstrated such as Oceanobacillus in salt crust, Nesterenkonia in sand, and Salinicoccus in the rhizosphere of the desert plant Salicornia. The collection was further evaluated for the production of extracellular enzymes. Activity tests showed that gram-positive bacteria were mostly active, particularly for protease, lipase, DNase, and amylase production. Our overall results demonstrate the huge phenotypic and phylogenetic diversity of haloalkaliphiles in saline systems of southern Tunisia which represent a valuable source of new lineages and metabolites.